Terorisme dan Demokrasi: Masalah Global, Solusi Lokal - Gabriel Lele (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Terrorism has become a real challenge to democracy. Despite all the costs it brings, however, measures to handle terrorism until the very recent times are less effective. Defensive measures are sometimes oversupplied while more aggressive ones are undersupplied. Both measures fail to reveal the very essential question of terrorism. Therefore, there needs to be an alternative way of looking at terrorism. Here, terrorism can be captured as an institutional problem at both national and international level. In this stance, terrorism can be put into democracy discourse where democracy is assumed to provide both incentive and constraint to terrorism. In such framework, democratic consolidation is urgently accomplished for terrorism to be eliminated from the society. Such measure is much more reliable and sustainable as it attacks the central question of terrorism in three areas concomitantly: institutional, behavioral, and performance aspects. Once these three aspects are realized, democracy will be the only game in town which consequently can eliminate terrorism.